Public policy and electrical-grid sector innovation. Issue 4 (2nd November 2015) - Rehme, Jakob; Nordigården, Daniel; Chicksand, Daniel
Abstract : Purpose: – This paper aims to investigate the manner in which technological innovation in the European electrical-grid sector has developed by focusing, in particular, on the effect of public policy on innovation. To achieve this aim, this paper highlights how technological innovation and development progressed from the 1960s to the 1980s, and contrasts this period with the deregulated/privatization environment. Design/methodology/approach: – The paper is based on a series of in-depth multiple company case studies of grid companies, some of their suppliers and other actors in their broader business network. Empirical data were collected through 55 interviews. Findings: – The authors find that a phase of mutual collaboration was encouraged in the first period, which led to strong technological innovation with a focus on product quality and the development of functionality. Buyers played a pivotal role in the development of products and posed technical requirements. In contrast, the current role of the buyer has transformed principally into one of evaluating competing bids for specific projects. Today, buyers face increasing pressure to substantially lower CO2 emissions and transform the energy grid system. These goals are difficult to achieve without a new way of thinking about innovation. Research limitations/implications: – Models to achieve innovation must not only focus on individual research projects; instead, the innovation should be factored into normal business dealings in the supply chain. Practical implications: – We propose that policymakers and regulators need to: accommodate for innovation and address the collaborative elements of innovation when developing policies and regulations. Furthermore, regulators have the option of either developing a strategic vision for the electrical-grid network or incorporating sustainability into the evaluation of electrical grids and, thus, consumers' willingness to pay. Originality/value: – This paper makes a distinctive contribution in the area of innovation for electrical grids. Our paper shows how innovation and the development of new technology for electrical grids changed over time. Furthermore, this paper describes the energy sector in terms of a business network comprising the different actors involved in innovation and development and, thus, their role in the energy supply chain.